THE MILLENNIAL KIAIS - Evi Fatimatur Rusydiyah; Halimatus Sa’diyah; Masykurotin Azizah (Epistemé: Jurnal Pengembangan Ilmu Keislaman, 2020)
The development of social media technology provides people with more accessible information about religious knowledge. Everyone can learn the religion from social media, particularly Youtube. This phenomenon seems to force young Nahdlatul Ulama (NU) kiais (religious experts) such as Gus Baha, Gus Miftah, and Gus Muwafiq to be more adaptive and familiar to social media platform, like Youtube. This makes them close to being called “the millennial kiais.” Using a phenomenological approach based on observations on Youtube, this paper examines the performance of millennial kiais in carrying out the process of dakwah (Islamic proselytization) and in becoming role models for social education as they do. The educational interaction carried out by these millennial kiais on Youtube seems to be very effective in attracting the interest of wider citizens. The number of their viewers reaches between four to eight million in one year. The number of videos viewed is around one hundred. The model of social education introduced by these millennial kiais is analyzed through the Bandura theory which starts through a process of stimulation and observation and is followed by a process in mental cognition, which creates motivation and demands a response by clicking the likes button and subscribing comments. The response marks the beginning of a constant change of behavior.